The easternmost tropical Pacific. Part II: Seasonal and intraseasonal modes of atmospheric variability - Amador, Jorge A. (2016)
This is Part II of a two-part review about climate and climate variability focused on the Eastern Tropical Pacific (ETP) and the Caribbean Sea (CS). Both parts are aimed at providing oceanographers, marine biologists, and other ocean scientists, a guiding base for ocean-atmosphere interaction processes affecting the CS, the ETP, and the waters of Isla del Coco. Isla del Coco National Park is a Costa Rican World Heritage site. Part I analyzed the mean fields for both basins and a larger region covering 25º S - 35º N, 20º W - 130º W. Here we focus on a smaller area (65º W - 95º W, 0º - 20º N), as a complement to Part 1. Incoming solar radiation and surface energy fluxes reveal the complex nature of the ETP and CS for convective activity and precipitation on seasonal and intraseasonal time scales. Both regions are relevant as sources of evaporation and the associated moisture transport processes. The American Monsoon System influences the climate and climate variability of the ETP and CS, however, the precise way systems affect regional precipitation and transport of moisture, within the Intra Americas Sea (IAS) are not clear. Although the Caribbean Low-Level Jet (CLLJ) is known to act as a conveyor belt for moisture transport, intraseasonal and seasonal modes of the CLLJ and their interactions with other IAS systems, have to be further investigated. Trans-isthmic jets, exert a variable seasonal wind stress force over the ocean surface co-generating regions of great marine productivity. Isolated convection, the seasonal migration of the Intertropical Convergence Zone, the hurricane season, the Mid-Summer Drought, the seasonal and intraseasonal behavior of low-level jets and their interactions with transients, and the southward incursion of cold fronts contribute to regional seasonal precipitation. Many large-scale systems, such as El Niño-Southern Oscillation, the Atlantic Multidecadal Oscillation and the Madden-Julian Oscillation (MJO, also influence the variability of precipitation by modulating regional features associated with convection and precipitation. Monthly tropical storm (TS) activity in the CS and ETP basins is restricted to the period May-November, with very few cases in December. The CS presents TS peak activity during August, as well as for the number of hurricanes and major hurricanes, in contrast to the ETP that shows the same features during September.